The quality of life of patients after mastectomy – analysis using the questionnaire QLQ-C30 - Benirowska, Sylwia (Pielęgniarstwo w Opiece Długoterminowej / Long-Term Care Nursing, 2018)
Introduction Breast cancer in Poland is a major cause of mortality in women. Early diagnosis and treatment prolongs life and affects the quality of life of women. Material and method The study was conducted among 100 patients. The study uses a questionnaire QLQ-C30. Most people with acute pancreatitis are between 41 and 60 years old. Among the factors contributing to the onset of the disease are the anti-health behaviors. Aim The aim of the study was is to determine the quality of life of patients after surgery mastectomy by Questionnaire QLQ-C30 . Material and methods The study was conducted among 100 patients. The study uses a questionnaire QLQ-C30. Results Women after amputation of the breast, have problems with family relations and sociable. There are also challenges in the execution of actions in everyday life. Women also spend attention to your appearance, self-perception after the amputation of the breast significantly affects the quality of life. Conclusions Conclusions presented in the work indicate a significant reduction in the quality of life of patients after mastectomy, these violations are observed at the level of physical and mental performance.